Pengaruh e-Promotion, Pelayanan, Kemudahan, e-WOM Terhadap Keputusan Pembelian, melalui Perilaku Konsumen pada Marketplace Lazada - Sugeng Lubar Prastowo; Ernie Mardiany Djaenudin; Nurul Vivi Apiyanti (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2023)
Lazada is an e-commerce with fewer visitors compared to other e-commerce. Several relevant research results show that there are still inconsistencies in research results. This study aims to determine the effect of e-Promotion, service quality, ease of shopping, and e-WOM on purchasing decisions through consumer behavior. The research method uses associative quantitative methods, with causal techniques. The sampling technique was purposive sampling, and data analysis was carried out both descriptively and inferentially. Analysis approach with SEM-PLS, using Smart PLS 3.0. The results of the study prove that the exogenous variables e-Promotion, convenience, and consumer behavior have a direct significant effect on purchasing decisions, while service quality, and e-WOM do not have a direct effect on purchasing decisions. As for e-Promotion, service quality, convenience, and e-WOM have a direct significant effect on consumer behavior. The e-Promotion variables, service quality, convenience, and e-WOM, have a significant indirect effect on purchasing decisions, through consumer behavior as a mediating variable.